Nutritional intake status of carpet weavers in Yazd-1390 - azadeh nadjarzadeh; Roghayeh zare reshkouyieh; gholamhossein Halvani; Reza Jafari Nodoushan (طب کار)
Background: Proper nutrition can affect the health status of next generation. Nutritional status of women workers is so important. This study has been done to determine energy, macro and micronutrient intakes and to compare with dietary standards. Methods: This descriptive cross sectional study has been done on 300 carpet weaver in Yazd. After measuring height and weight, dietary intake was determined using 3 day 24 h dietary recall questionnaire and analyzed by Nutritionist 4 software. Descriptive analysis and t-test were used by SPSS software. Results: After omitting over and under reporting, data of 170 workers were analyzed. Mean of body mass index was 23.39±3.84 Kg/m2. Mean of energy intake was 2536.4±473.7 Kcal/d while 55.65, 10.86, and 33.48 percents of energy have been supplied by carbohydrate, protein and fat, respectively. Dietary intakes of vitamin A and C were significantly lower than Dietary Reference Intakes (DRI). Energy excess was seen in 91.7 percent of women and 31.8 percent of them were obese or overweight. Conclusion: according to this study, micronutrient deficiencies are the issue in women in spite of energy excess.